Catching a Liar Through Facial Expression of Fear - Shen, Xunbing; Fan, Gaojie; Niu, Caoyuan; Chen, Zhencai (Frontiers in Psychology, 2021)
High stakes can be stressful whether one is telling the truth or lying. However, liars could feel extra fear from worrying to be discovered than truth-tellers, and according to leakage theory, the fear is almost impossible to be repressed. Therefore, we assumed that analyzing the facial expression of fear could reveal deceits. Detecting and analyzing the subtle leaked fear facial expressions is a challenging task for laypeople. It is, however, a relatively easy job for computer vision and machine learning. To test the hypothesis, we analyzed video clips from a game show “The moment of truth” by using OpenFace (for outputting the Action Units of fear and face landmarks) and WEKA (for classifying the video clips in which the players was lying or telling the truth). The results showed that some algorithms achieved an accuracy of greater than 80% merely using Action Units of fear. Besides, the total duration of Action Unit 20 of fear was found to be shorter under the lying condition than that from the truth-telling condition. Further analysis found that the reason for a shorter duration in the lying condition was that the time window from peak to offset of Action Unit 20 under the lying condition was less than that under the truth-telling condition. The results also showed that facial movements around the eyes were more asymmetrical when people are telling lies. All the results suggested that facial clues can be used to detect deception, and fear could be a cue for distinguishing liars from truth-tellers.